Android For Dummies, 2nd Edition - Gookin, Dan (--For dummies., 2020)
Set up, configure, and get connected Shoot and share photos and videos Use social media, text, and email to stay in touch Make the most of your Android gizmo Be honest-isn't "gizmo" a friendlier word than "device"? This book will tell you pretty much everything you need to know about your Android smartphone or tablet in an equally friendly manner, because that's the best way to learn how to get the most from your Android. From buying, unpacking, and setting up your gizmo to managing calls and email, posting to social media, navigating with Maps, and creating a photo slideshow, it's like having a good friend show you the basics and explain how to take advantage of all the cool stuff. Inside... All about Android 10 Updated security features Customizing your Android Creating multimedia messages Apps to help you get social The Bluetooth connection Exploring Google Play Essential troubleshooting tips.